AN ANALYSIS ABOUT SLANG LANGUAGE IN THE SONG LYRICS OF THE BLACK EYED PEAS (BOOM BOOM POW, IMMA BE, PUMP IT, SHUT UP, AND MY HUMPS) - Arini Hidayah; Febryan Bayu Ramadhan (Universitas Musamus, 2020)
This research concerns the analysis of slang in the song lyrics of The Black Eyed Peas entitled Boom Boom Pow, Imma Be, Pump It, Shut Up, My Humps. The are two objectives in this research, namely to tell types of the slang appeared in this song, and to explain the meaning of slang. This analysis use descriptive method due to the fact that this research describe the meaning of the slangs. The data were taken from the song lyrics of The Black Eyed Peas entitled Boom Boom Pow, Imma Be, Pump It, Shut Up and My Humps. The researcher uses document and records method to gather the data which is by taking note of the slangs appeared in this song, then classifying them by their types, after that explaining their meaning, the researcher analyzing the meanings of the slang using an American Slang Dictionary and the researcher also asked the help of a Native American in analyzing the meanings of slang, finally, give a conclusion. The researcher found there are 37 total data of slangs in the song lyrics of The Black Eyed Peas entitled Boom Boom Pow, Imma Be, Pump It, Shut Up and My Humps. Then there are 37 total data of the meaning of slangs in the song lyrics of The Black Eyed Peas entitled Boom Boom Pow, Imma Be, Pump It, Shut Up and My Humps.